The Effectiveness of the Implementation of the Village and Community Fund Policy in the Area of Nakhon Pathom sub-district, Mueang Nakhon Pathom district, Nakhon Pathom Province: ประสิทธิผลของการดำเนินงานตามนโยบายกองทุนหมู่บ้านและชุมชนเมือง ในพื้นที่ตำบลนครปฐม อำเภอเมืองนครปฐม จังหวัดนครปฐม - แจ่มสว่าง, เชาวลิต (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
The purpose of this study to 1) study the level of effectiveness of the implementation of the village and community fund policy in the area of Nakhon Pathom sub-district, Mueang Nakhon Pathom district, Nakhon Pathom Province, 2) study the factors in the implementation of the village and community fund that are related to the effectiveness of the implementation of the village and community fund policy in the area of Nakhon Pathom sub-district. The sample group used in this research was 130 people household representatives in the area of Nakhon Pathom sub-district, Mueang Nakhon Pathom district, Nakhon Pathom Province by utilizing questionnaires as a tool for data collection. Data analysis used descriptive statistics including percentage, mean, standard deviation. And inferential statistics include chi-square statistics, multiple regression analysis. The results of the study showed that 1) the effectiveness of the implementation of the village and community fund policy in the area of Nakhon Pathom sub-district, Mueang Nakhon Pathom district, Nakhon Pathom Province in the overall image was at a moderate level, which is arranged in the following order: (1) Economic stimulation in villages and urban communities, (2) Being a source of working capital for the villagers, (3) Self-reliance of villagers in the operation of the fund, (4) Fund management to villagers in the community, 2) Factors in the implementation of the policy of the village and community fund are related to the effectiveness of the implementation of the village and community fund policy in the area of Nakhon Pathom sub-district, Mueang Nakhon Pathom district, Nakhon Pathom Province found that the factors in operation according to the policy of the village and community fund, in the aspect of personnel, knowledge, understanding, attitude, communication, and participation have a rational relationship with the effectiveness of the implementation of the village and community fund policy in the area of Nakhon Pathom sub-district, with a statistical significance level of .05.